2010
DOI: 10.1002/pa.352
|View full text |Cite
|
Sign up to set email alerts
|

Leaders without ethics in global business: Corporate psychopaths

Abstract: This paper introduces the concept of Corporate Psychopaths as ruthless employees who can successfully gain entry to organizations and can then get promoted within those organizations to reach senior managerial and leadership positions. What little empirical research currently exists supports the view that Corporate Psychopaths are more commonly found at senior levels of organizations. This paper presents further empirical evidence that supports this view. It discusses how, in a quantitative sample of 346 white… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(81 citation statements)
references
References 64 publications
(88 reference statements)
2
77
0
1
Order By: Relevance
“…Similarly Clarke and other psychologists describe Corporate Psychopaths as typically being recognized as being toxic leaders by their followers but not by their superiors (Babiak, 1995;Babiak et al, 2006;Boddy, 2011c;Boddy, Ladyshewsky, & Galvin, 2010b;Clarke, 2005Clarke, , 2007, which is exactly how the Corporate Psychopath managers were regarded in this research among HR Directors.…”
Section: "He Managed the Relationship In A Charming Fashion Entirely mentioning
confidence: 59%
See 1 more Smart Citation
“…Similarly Clarke and other psychologists describe Corporate Psychopaths as typically being recognized as being toxic leaders by their followers but not by their superiors (Babiak, 1995;Babiak et al, 2006;Boddy, 2011c;Boddy, Ladyshewsky, & Galvin, 2010b;Clarke, 2005Clarke, , 2007, which is exactly how the Corporate Psychopath managers were regarded in this research among HR Directors.…”
Section: "He Managed the Relationship In A Charming Fashion Entirely mentioning
confidence: 59%
“…Their characteristics of being ultra-rational, financially oriented managers with no emotional concern for or empathy with other employees or their welfare (Boddy, Galvin, & Ladyshewsky, 2009), marks them as apparently useful to the style of "Chicago School" capitalism (Friedman, 1970) that is merely profit oriented. This role as agents of capitalism without a conscience marks Corporate Psychopaths as worthy of further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…These findings may, however, be explained by the low prevalence of individuals with notably high psychopathy levels among the general population (estimated to be about 1%; Boddy, Ladyshewsky, & Galvin, 2010), thus relationships between psychopathy and ‗life success' may be less visible at population level. Furthermore, factors such as age and gender, PSYCHOPATHY DISCIPLINE CHOICE SUCCESS 5 potentially important confounding factors of the psychopathy-life-success relationship were not controlled for.…”
Section: Ulrich Et Al (2008) Investigated the Relationship Between Pmentioning
confidence: 95%
“…The manipulative nature of corporate psychopaths is a least obvious trait that allows them to gain the confidence of other people, expedites their progression in corporate ranks and provides ample leverage to harm their organizations (Mahaffey and Marcus, 2006). Studies by Boddy (2011a), Boddy et al (2010), found that most corporate psychopaths belong to senior management positions of organizations and their actions at this level can be extremely damaging, especially when organizational culture is weak.…”
Section: Corporate Psychopathymentioning
confidence: 99%